PROSES PEMBELAJARAN BAHASA INDONESIA BERBASIS MANAJEMEN KELAS BAGI PENUTUR ASING (BIPA) PROGRAM DARMASISWA (Penelitian Kualitatif Deskriptif Program BIPA Darmasiswa di UPT BALAI BAHASA UPI) - Deti Rostini; Aam Aminah (Media Nusantara, 2019)
The study concerns the investigation of class management in the process ofIndonesian as a Foreign Language (IAFL) learning in Darmasiswa program.It is conducted in order to explore class management of IAFL program, fromplanning, organizing, implementing, to evaluating process. It is also to describeobstacles and solutions taken in the process of class management. The studywas carried out in the Language Center of Indonesia University of Education,involving two IAFL teachers, two IAFL students, one IAFL coordinatorand one staff of university International Office. By employing three types ofinstruments, including observation, interview and document study, this studyfound that in general, Darmasiswa program in the Language Center of UPIis well managed. It can be seen from several aspects; (1) Well-organized planinvolving all management aspects, (2) A clear organization between the tasksdone by International Office, Coordinator (management and teaching program,and Teacher in the center (class management and class teaching learning); and(3) Teacher’s skills in managing class, viewed from the way opening the class,embracing the students coming from different culture and with different paces inone level, using varying methods and techniques, evaluating, making use of and optimizing the existing facilities, as well as overcoming obstacles using good efforts have been proven to result in a good class management.